Basal Encephalocele-an Uncommon Cause of Respiratory Distress in Newborn - Gurung, Binay; Gurung, Urmila; Shrestha, Laxman (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Basal encephalocele is one of the important causes of respiratory distress in newborn, although uncommon and hence under emphasized. It is a form of neural tube defect that usually presents with symptoms of nasal obstruction. Delayed presentation with variable symptoms have been noted. Collaborative surgical intervention is the treatment modality with different approaches. However, intervention early in neonatal period is a challenge in our region with resource limitations. Prognosis is worse with associated malformations and chromosomal anomalies. We report two cases of newborn with basal encephalocele presenting as respiratory distress at birth.Nepalese Journal of ENT Head and Neck Surgery, Vol. 5, No. 2, 2014, Page: 18-20